Transition into democracy and Catholic Church in Spain. The Govern of reformation - Martín de Santa Olalla Saludes, Pablo (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
The designation of Adolfo Suárez for presidency of Spanish Government in july of 1976 opened a new perspective of Catholic Church-State relations, sized till that time by a rigid confesionality who had been broken by a «basic» agreement in which it was determined the way to design bishops and lost of juridic immunity of Catholic Church in Spain. The main purpose of this article is making know the second phase of negotiation that turned to the definitive separation between Catholic Church and State in Spain, with aconfesionality as end of that process.
Keywords: reformation; Concordat; agreements; Holy See; Spanish Government